An Ag2S@ZnS‐coated fiber for efficient, long‐life solid‐phase microextraction of polycyclic aromatic hydrocarbons in water. Issue 18 (3rd September 2020) - Liu, Hongmei; Fan, Hua; Wang, Xiaoqi; Dang, Shihao; A, Gu
Abstract: Although an efficient and stable fiber coating is essential for the development of solid‐phase microextraction technique, it remains a challenging prospect. Herein, an inorganic nanocomposite material Ag2 S@ZnS was prepared and used as a coating for fibers to detect polycyclic aromatic hydrocarbons in water samples in combination with a GC with flame ionization detector. Compared with a single ZnS material, the Ag2 S@ZnS composite shows many uneven nano‐protrusions on the surface of the microspheres. In conjunction with the relatively scattered microstructure of the coating and the effective anion‐π interaction formed between ZnS and the hydrocarbons, it has a large specific surface area, fast diffusion of the target molecule on its surface, and appropriate adsorption of the target molecules; therefore, it exhibits good extraction efficiency for the hydrocarbons. Under optimal conditions, the proposed analytical method exhibits superior performance with good linearity (0.01–500 µg/L) and low limits of detection (0.001–0.200 µg/L). Combined with high thermal, chemical, and mechanical stability, the service life of the coating was improved and could be used 200 times without a significant reduction in the extraction performance, and at least 2000 extraction–desorption cycles can be achieved. Satisfactory results were also obtained for the real samples.